Challenges and benefits of digital workflow implementation in aerospace manufacturing engineering - Rojo Abollado, Jaime; Shehab, Essam; Bamforth, Philip (Elsevier, 2017)
Companies who operate in highly regulated industries have further challenges to the usual competition, continuous cost reduction and product development challenges. To address these requirements companies optimise their business processes and change their applications and information systems to support their evolving way of doing business. Workflow management technology eases the achievement of these necessities by providing methodologies, software and tools to support business process modelling, reengineering and workflow automation. Business process mapping is necessary in order to capture business processes as workflow specifications. Then, these systems allow business process reengineering, helping the optimisation of specified processes, and workflow automation, in order to generate a lean digital workflow from the specifications. There are many opportunities to benefit from this technology in aerospace applications, however these bring several implementation challenges in large global companies operating in multiple markets and need to be carefully managed. This research provides an overview of the benefits that digital workflows implementation can potentially bring to aerospace companies, together with a detailed description of significant challenges, regarding both the implementation of digital workflows and risks related to human factors. The study increases industry awareness on the importance of driving a digital transformation through implementing digital workflows, and where to start this implementation in a manufacturing business, highlighting the success factors.
Keywords: Digital workflows; Workflow management; Business process optimisations; Digitisation; Complexity management